COVID-19 point-of-care testing in care homes: what are the lessons for policy and practice?. (12th May 2021) - Buckle, Peter; Micocci, Massimo; Tulloch, John; Kierkegaard, Patrick; Parvulescu, Paula; Thompson, Carl; Spilsbury, Karen; Allen, A Joy; Body, Richard; Hayward, Gail; Buchan, Iain; Gordon, Adam L
Abstract: COVID-19 has devastated care homes. Point-of-care tests (POCTs), mainly using lateral flow devices (LFDs), have been deployed hurriedly without much consideration of their usability or impact on care workflow. Even after the pandemic, POCTs, particularly multiplex tests, may be an important control against spread of SARS-CoV-2 and other respiratory infections in care homes by enabling identification of cases. They should not, however, replace other infection control measures such as barrier methods and quarantine. Adherence to LFDs as implemented among care home staff is suboptimal. Other tests—such as point-of-care polymerase chain reaction and automated antigen tests—would also need to be accommodated into care home workflows to improve adherence. The up-front costs of POCTs are straightforward but additional costs, including staffing preparation and reporting processes and the impacts of false positive and negative tests on absence rates and infection days, are more complex and as yet unquantified. A detailed appraisal is needed as the future of testing in care homes is considered.